Extending the boundaries of the Declaration of Helsinki: a case study of an unethical experiment in a non-medical setting. Issue 2 (1st April 2001) - Richter, Elihu D; Barach, Paul; Berman, Tamar; Ben-David, G; Weinberger, Zvi
Abstract : To examine the ethical issues involved in governmental decisions with potential health risks, we review the history of the decision to raise the interurban speed limit in Israel in light of its impact on road death and injury. In 1993, the Israeli Ministry of Transportation initiated an "experiment" to raise the interurban speed limit from 90 to 100 kph. The "experiment" did not include a protocol and did not specify cut-off points for early termination in the case of adverse results. After the raise in the speed limit, the death toll on interurban roads rose as a result of a sudden increase in speeds and case fatality rates. The committee's decision is a case study in unfettered human experimentation and public health risks when the setting is non-medical and lacks a defined ethical framework. The case study states the case for extending Helsinki type safeguards to experimentation in non-medical settings.